(untitled) (Technological Innovations Journal, 2024)
It is difficult to imagine that the COVID-19 pandemic has generated any benefit or positive effect on the lives of human beings. Many people have suffered the loss of family and friends, added to this the fact that the audiovisual media and social networks have been bombarded with negative news highlighting the mass death and negative consequences of the pandemic. This article has a mixed approach, of a phenomenological paradigm with a non-experimental design. An online survey was applied to 65 workers from public and private companies and 15 interviews were conducted with key collaborators who voluntarily agreed to participate in the year 2022. To analyze the quantitative data, the statistical software IBM SPSS Statistics Version 25 was used. The data they were subjected to normality tests, with a result of P= 0.000 (P < 0.05), for which the non-parametric Spearman’s Rho test was used. The statistical software ATLAS.ti version 9 was used to analyze the qualitative data. In conclusion, the COVID-19 pandemic has had a significant negative impact worldwide and it is important to recognize and address these consequences. However, it is also true that the pandemic has generated some positive changes in different areas, and it is possible to take advantage of these changes to build a more sustainable and resilient future.